2016
DOI: 10.1210/jc.2015-4252
|View full text |Cite
|
Sign up to set email alerts
|

PDE5 Inhibition Ameliorates Visceral Adiposity Targeting the miR-22/SIRT1 Pathway: Evidence From the CECSID Trial

Abstract: Treatment with PDE5i in humans and murine models of diabetes improves VAT, targeting SIRT1 through a modulation of miR-22-3p expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 41 publications
4
42
0
Order By: Relevance
“…In vivo administration of antagomir of miR-22 to spontaneously hypertensive rat reduced blood pressure and revealed a new avenue for treatment of hypertension50. We recently demonstrated that sildenafil determined a downregulation of circulating miR-22 in diabetic patients and in adipose tissue of db/db mice31. In the present study, we confirmed the downregulation of miR-22 by sildenafil in diabetic kidney and upregulation of its target BMP7, associated with tissue protection.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In vivo administration of antagomir of miR-22 to spontaneously hypertensive rat reduced blood pressure and revealed a new avenue for treatment of hypertension50. We recently demonstrated that sildenafil determined a downregulation of circulating miR-22 in diabetic patients and in adipose tissue of db/db mice31. In the present study, we confirmed the downregulation of miR-22 by sildenafil in diabetic kidney and upregulation of its target BMP7, associated with tissue protection.…”
Section: Discussionsupporting
confidence: 83%
“…It was previously demonstrated that BMP7 is regulated by miR-2230. In light of the observed downregulation of miR-22 in adipose tissue after sildenafil treatment31, we decided to verify whether miR-22 underwent a similar pattern of downregulation in kidney. To this end, we examined miR-22 expression by qPCR, finding that it was downregulated by sildenafil ~3 fold ( P  < 0.001), (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In this study, we confirmed in the SAT depot the results of sildenafil treatment found in VAT on macrophages and ECs . Additionally, we found that PDE5 activity is required for CCL2 and IFN-γ expressions in AT, and sildenafil may be able to suppress chronic inflammation in obesity by inhibiting the expres- In VAT of obese diabetic mice, we observed that PDE5i led to a significant increase in APs, which indicated a propensity to AT hyperplasia rather than hypertrophy (Fiore, Gianfrilli, et al, 2016).…”
Section: Discussionmentioning
confidence: 72%
“…Finally, recent data showed that PDE5 inhibitor treatment in humans reduces EF and upregulates SIRT1 in both serum and subcutaneous fat, opening novel therapeutic strategies for EF remodeling and regulation of SIRT1 to promote healthier fat deposits [36].…”
Section: Discussionmentioning
confidence: 99%